2024
DOI: 10.1007/s11103-024-01437-w
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the cell-wall dynamics in grapevine berries during ripening and in response to biotic and abiotic stresses

Giulia Malacarne,
Jorge Lagreze,
Barbara Rojas San Martin
et al.

Abstract: The cell wall (CW) is the dynamic structure of a plant cell, acting as a barrier against biotic and abiotic stresses. In grape berries, the modifications of pulp and skin CW during softening ensure flexibility during cell expansion and determine the final berry texture. In addition, the CW of grape berry skin is of fundamental importance for winemaking, controlling secondary metabolite extractability. Grapevine varieties with contrasting CW characteristics generally respond differently to biotic and abiotic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 138 publications
0
1
0
Order By: Relevance
“…Previous studies have found that NST can thicken the secondary cell wall of Populus and Arabidopsis [ 40 , 41 ], and the change of the secondary cell wall can enhance grapevine and Populus resistance to abiotic stress [ 42 , 43 ]. By observing the cross-section of transgenic tobacco, it was found that compared with CK, the secondary cell wall thickness of transgenic tobacco has changed to a certain extent and the resistance to abiotic stress has been enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that NST can thicken the secondary cell wall of Populus and Arabidopsis [ 40 , 41 ], and the change of the secondary cell wall can enhance grapevine and Populus resistance to abiotic stress [ 42 , 43 ]. By observing the cross-section of transgenic tobacco, it was found that compared with CK, the secondary cell wall thickness of transgenic tobacco has changed to a certain extent and the resistance to abiotic stress has been enhanced.…”
Section: Discussionmentioning
confidence: 99%